FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KETERATURAN IBU HAMIL DALAM MENGKONSUMSI TABLET FE DI WILAYAH KERJA PUSKESMAS SULIT AIR KABUPATEN SOLOK - Herawati, Netty (Ensiklopedia Education Review, 2019)
Pregnancy is a condition in which the fetus is conceived in the mother's body, which begins with the fertilization process. Lack of iron during pregnancy will lead to iron deficiency anemia and can cause bleeding during delivery, facilitate infection and decrease the carrying capacity of acid. The need for pregnant women for Fe increases (for the formation of placenta and red blood cells) by 200-300%, about 300 mg of Fe is transferred to the fetus so that 50-75 mg for the formation of placenta, 450 mg for increasing the amount of red blood and 200 mg disappears when The type of research in this research is descriptive analytic using cross sectional design. In this study, the independent variables are motivation, the role of health workers and family support, the dependent variable is the regularity of consuming Fe tablets. Based on the statistical test, it was obtained p value 0.007 Ë‚ 0.05, which means that there is a significant relationship between poor motivation and irregularity in consuming Fe tablets in the working area of Puskesmas with difficult water. Based on statistical tests, p value is 0.001 0.05, which means there is a significant relationship There is a significant difference between the role of health workers and irregularity in consuming Fe tablets in the working area of Puskesmas with difficulty in water. Based on statistical tests, the p value is 0.000 Ë‚ 0.05, which means that there is a significant relationship between poor family support and irregularity in consuming Fe tablets in the region. The Work of Puskesmas is Hard to Water.